2021
DOI: 10.21203/rs.3.rs-747227/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High burden of hypovitaminosis D among the children and adolescents in South Asia: A systematic review and meta-analysis

Abstract: Background: Vitamin D is vital for the growth and development of children. While deficiency and/or insufficiency of vitamin D among South Asian children are frequently reported in the literature, the lack of a meta-analysis has left its true extent poorly characterized. In this study, we aimed to conduct a systematic review and perform meta-analyses of the prevalence of hypovitaminosis D among the children of the South Asian countries.Methods: Two major electronic search engines (PubMed and Scopus) and one dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
4
1
Order By: Relevance
“…Therefore, any interpretations should be observational, at best (59) . Our results are higher than the pooled serum vitamin D levels in South Asian children and adolescents (19.15 ng/mL) (16) but lower than in African children (28.88 ng/mL) (52) . Numerous factors affect the serum vitamin D levels besides the factors mentioned previously, such as dietary and vitamin D supplement intake (10) , body mass index, physical activity (60) , genetic influences (61,62) , and infection status (63) .…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 84%
See 3 more Smart Citations
“…Therefore, any interpretations should be observational, at best (59) . Our results are higher than the pooled serum vitamin D levels in South Asian children and adolescents (19.15 ng/mL) (16) but lower than in African children (28.88 ng/mL) (52) . Numerous factors affect the serum vitamin D levels besides the factors mentioned previously, such as dietary and vitamin D supplement intake (10) , body mass index, physical activity (60) , genetic influences (61,62) , and infection status (63) .…”
Section: A C C E P T E D a R T I C L Econtrasting
confidence: 84%
“…children and adolescents have low serum vitamin D (50) . Other studies have also confirmed this phenomenon (16,54) . One possible explanation for this is that Southeast Asian females practice traditional heavy clothing such as hijab or shari), concealing their skin from possible sources of ultraviolet (UV) light (55) .…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 55%
See 2 more Smart Citations
“…In Bangladesh, the child mortality rate was much higher at the decade of independence in 1971 24 . The cause behind this was various infectious diseases 25,26 . Since then, Bangladesh government had been started an extensive immunisation programme (EPI) across the country in order to protect the child from these diseases 27–30 .…”
Section: Discussionmentioning
confidence: 99%